(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Juvenile Delinquency is a prevalent issue in the community, with adults disappointed and afraid that children from broken families are not eligible to be imprisoned. Preventive Measures for Juvenile Delinquency aim to explain the relationship between broken Families and Juvenile Delinquency and promote action plans to prevent further damage. Economic difficulties, such as poverty, can increase the risk of delinquency for children from broken homes. Since 2020, there has been an increase in youth violence nationwide. To help children from broken homes succeed, it is crucial that parents, educators, and policymakers address these problems and offer support and resources. Researchers agreed that family counseling and child assessments are crucial components in preventing broken families and juvenile delinquency, as well as conducting seminars and other forms of recreation. The findings showed that a moderate amount of data affirms the idea that a broken family is associated with a higher risk of juvenile delinquency. It has also been observed that inadequate parental supervision has a significant impact on juvenile delinquency, particularly when the parent exhibits excessive permissiveness and is unable to control the use of substances like alcohol. This causes the child to feel neglected and emotionally deprived, which causes them to behave inappropriately outdoors and at school. Broken families and juvenile delinquency have been studied extensively, and research has shown that children from broken families are at a higher risk of participating in delinquent conduct than those from intact homes. This association has been shown in people of all cultures, socioeconomic groups, and family structures and is due to the absence of parental control and direction. Children who experience this neglect may act out or engage in risky behavior in an effort to gain attention.